Penggunaan Fermentasi Daun Pepaya (Carica Papaya), Kunyit (Curcuma Domestica Val.), dan Garam (Nacl) dalam Menunjang Pertumbuhan dan Kelangsungan Hidup Ikan Lele pada Budidaya Ikan dalam Ember (Budikdamber) - Maria Menciana Moniz; Yuliana Salosso; Ridwan Tobuku (Nusa Cendana University, 2026)
The Bucket Fish Farming System (Budikdamber) has emerged as a practical and environmentally sustainable aquaculture method for small-scale fish production. Nevertheless, its productivity largely depends on efficient feed utilization and maintaining fish health. Fermented mixtures prepared from papaya leaves, turmeric, and salt have attracted attention as natural feed supplements that may enhance fish growth performance. This study evaluated the effects of fermented papaya leaves, turmeric, and salt on the growth performance, feed utilization efficiency, survival rate, and water quality of African catfish (Clarias gariepinus) cultured in a Budikdamber system. A one-month experiment was conducted using a Completely Randomized Design consisting of three treatments with three replicates: a control without fermented supplementation, supplementation with 4 mL of fermented solution, and supplementation with 40 mL of fermented solution. Growth performance was assessed through absolute length gain and absolute weight gain, while feed conversion ratio, survival rate, and water quality were also evaluated. The results demonstrated that fermented supplementation significantly improved fish growth and feed utilization. The application of 40 mL fermentation produced the highest absolute length gain (11.53 ± 0.31 cm) and absolute weight gain (127.35 ± 4.49 g), together with the lowest feed conversion ratio (1.30 ± 0.49), indicating superior feed efficiency. Survival remained consistently high across all treatments (98.33–100%), and the measured water quality parameters stayed within the acceptable range for African catfish culture. These findings suggest that supplementation with 40 mL of fermented papaya leaves, turmeric, and salt is an effective approach to improving growth performance and feed utilization efficiency in African catfish reared under the Budikdamber culture system. Keywords: African catfish, Budikdamber, feed conversion ratio, fermented papaya leaves, growth performance, turmeric.